DAMPAK PANDEMI COVID 19 TERHADAP PROSES PENGAJARAN DI SD NEGERI 118273 MAMPANG KECAMATAN KOTAPINANG KABUPATEN LABUHAN BATU SELATAN - Rahmadani Tanjung (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractOne way to break the chain of the spread of Covid 19 is by limiting interaction with the community which is applied to inhibit the rate of growth in various fields of life, both in the economic, social and of course education. The government's decision to dismiss students, move the teaching and learning process at school to be at home. Some local governments decided to implement a policy of laying off and starting to implement online learning (online) or through an online system. The temporary closure of educational institutions to contain the spread of the Covid 19 pandemic in Indonesia nationally has an impact on millions of students. Disturbances in the learning process directly between students and teachers and the cancellation of learning assessments have an impact on the psychology of students and reduce the quality of students' learning skills. This article aims to identify the impact of the Covid 19 pandemic on teaching conducted by teachers. This study shows that there are several obstacles experienced by students, teachers and parents in learning activities, namely the mastery of technology is still lacking, the addition of internet communication quota costs for students, parents and teachers is reduced; and unlimited working hours for teachers because they have to communicate and coordinate with parents, other teachers and school principals. Keywords: Pandemic covid 19, Online Teaching